A modified power decoupling control strategy for a grid-connected inverter with a low switching frequency under unbalanced grid voltages. (August 2022) - Wu, Fuyun; Liu, Rui; Xie, Yanyu; Lyu, Jianguo
Abstract: In the photovoltaic grid-connected power generation system, when proportional resonant (PR) control is adopted for the grid-side inverter in the two-phase stationary coordinate ( α β ), there is a coupling problem between active power (P) and reactive power (Q). Under unbalanced grid conditions, especially in high-power applications where the switching frequency of the grid inverter needs to be reduced, the power coupling problem will be exacerbated. Based on the instantaneous power response characteristics of the grid inverter, expressions of the power coupling coefficient under unbalanced power grids are derived in this paper, and the influence of the unbalanced grid voltage on the power coupling is revealed. Moreover, a decoupled grid-side model of the grid inverter is established, and a modified controller based on positive and negative sequence (P–N sequence) decoupling is proposed to solve the power coupling problem. The closed-loop transfer function of the system with the modified current controller is studied, and the stability of the modified controller is analyzed according to the bilateral frequency response diagram. Based on analysis of the coupling coefficient, the degree of coupling between P and Q can be reduced significantly by applying the proposed control method. Furthermore, in order to solve the influence of the delay on the power coupling caused by the low switching frequency, the decoupling compensation link for the delay is introduced, which can eliminate the influence of delay on power coupling. Finally, experiments are performed on a grid-connected inverter prototype. The experimental results show that when the grid voltage is unbalanced, the proposed control method can reduce the coupling degree of the P and Q, which also improves the dynamic performance of the grid-connected inverter with a low switching frequency.